2019
DOI: 10.1088/1742-6596/1179/1/012039
|View full text |Cite
|
Sign up to set email alerts
|

Application of Multimedia Animation Engineering Drawing (MMAED) for Vocational High School Students

Abstract: The use of animated multimedia in vocational schools in Indonesia is still not optimal, this is due to the lack of innovative teaching materials, especially multimedia-based instructional materials. This study aims to apply the results of the development of innovative teaching materials based on engineering animated image Multimedia for Vocational High Schools especially in the competence of Mechanical Engineering expertise. Meanwhile, the specific objectives to be achieved in this study are: (1) applying inno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Therefore, it was recommended that lecturers should use this method in teaching, especially for certain topics in technical drawings that required students to master visualization skills. Mujiarto, Komaru, Pratiwi, Muhammad, and Sayuti (2019) found that media learning utilization in the form of multimedia animation of technical drawings increased the mechanical engineering skills of students, especially in drawing materials for orthographic projections, and improved their competence. Moreover, the use of audio-visual media in learning received positive perceptions from teachers and students as stated by Shabiralyani, Hasan, Hamad, and Iqbal (2015) showed that most teachers and students had positive perceptions concerning the use of audio-…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it was recommended that lecturers should use this method in teaching, especially for certain topics in technical drawings that required students to master visualization skills. Mujiarto, Komaru, Pratiwi, Muhammad, and Sayuti (2019) found that media learning utilization in the form of multimedia animation of technical drawings increased the mechanical engineering skills of students, especially in drawing materials for orthographic projections, and improved their competence. Moreover, the use of audio-visual media in learning received positive perceptions from teachers and students as stated by Shabiralyani, Hasan, Hamad, and Iqbal (2015) showed that most teachers and students had positive perceptions concerning the use of audio-…”
Section: Discussionmentioning
confidence: 99%